Ensino bilíngue e escrita da língua portuguesa em Moçambique: Bilingual teaching and Portuguese language writing in Mozambique - M. Abdula, Rajabo Alfredo (Universidade de Integração Internacional da Lusofonia Afro-Brasileira, 2021)
Matapulelo: Masunziyo a Echuwabo eswa Moçambique. Masaka mendjene malogelo a ezugu aikana owaddela malogelo aba tharo zetezene za masunzi. Oroma wa masunzo a Echuwabo na ezugo a thiya maloguelo a ekafiri a Moçambique aikala maloguelo a masunziyo M'maxikola mum m'padduwa massunzo a Echuwabo vina munopadduwa masunzo a ezugo enkosiya wi aima ainlogoa ezugu anosunza alogaga maloguelo a obaliwana. Attu ena anokodda massunzo a ekafiri, na vina anamasunziya ena na ababi anowova wi aima kanaakabe oziwelamo onligana na ansunza ezugu, na vina enowalibiya ababi ena aburuchagawo anawa mwa masunzo a Echuwabo para ezugu. Nonaga makalelo aba ni ubuwela oveda ononelamo na malago zai (i) opima oleba na ezugu wa anamasunza a Echuwabo, (ii) wangana akala ookala ottaganyiyeya wa Echuwabo na malebelo a ezugu, (iii) opima malebelo a anasikola a Echuwabo na ezugu. Na ttagi ya waddeliwa okosiwe na anasikola a ezugo na ena a ekafiri eifanyela wonelamo anasikola a Echuwabo na vina a ezugu awoniya malebelo a deretu a ezugu; kaiyoneylevo ottaganyiyeya mwa malebelo a ezugu anamasunza a Echuwabo na vina malebelo a anamasunza Echuwabo ali midhidha zimozazene na anamasunza ezugu. *** Bilingual education is still recent in Mozambique. For a long time, the Portuguese language had a monopoly of use as a teaching medium in all classes and levels of education. The introduction of bilingual education allowed some Mozambican languages to be used as a teaching medium. In schools where bilingual education takes place, there is also monolingual teaching, which means that children who do not speak Portuguese learn using their mother tongue. Some people are skeptical about bilingual education, including some teachers and parents of students who fear that their children will not have the same education as children in monolingual education, which causes some parents to withdraw their children from bilingual education to monolingual education. Taking into account this situation, we decided to carry out this research, which aimed to (i) analyze the Portuguese ...